Deciphering Autoimmune Pancreatitis, a Great Mimicker: Case Report and Review of the Literature - Satya Allaparthi; Mohammed Sageer; Mark J. Sterling (Case Reports in Gastrointestinal Medicine)
Background. Autoimmune pancreatitis (AIP) is an atypical chronic inflammatory pancreatic disease that appears to involve autoimmune mechanisms. In recent years, AIP has presented as a new clinical entity with its protean pancreaticobiliary and systemic presentations. Its unique pathology and overlap of clinical and radiological features and absence of serological markers foster the disease’s unique position. We report a case of diffuse type 1 autoimmune pancreatitis with obstructive jaundice managed with biliary sphincterotomy, stent placement, and corticosteroids. A 50-year-old Caucasian woman presented to our hospital with epigastric pain, nausea, vomiting, and jaundice. Workup showed elevated liver function tests (LFT) suggestive of obstructive jaundice, MRCP done showed diffusely enlarged abnormal appearing pancreas with loss of normal lobulated contours, and IgG4 antibody level was 765 mg/dL. EUS revealed a diffusely hypoechoic and rounded pancreatic parenchyma with distal common bile duct (CBD) stricture and dilated proximal CBD and common hepatic duct (CHD). ERCP showed tight mid to distal CBD stricture that needed dilatation, sphincterotomy, and placement of stent that led to significant improvement in the symptoms and bilirubin level. Based on clinical, radiological, and immunological findings, a definitive diagnosis of AIP was made. Patient was started on prednisone 40 mg/day and she clinically responded in 4 weeks.